1982
DOI: 10.1136/jnnp.45.9.844
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anticonvulsant drugs on the development of male rats and their fertility.

Abstract: SUMMARY Albino male rats were injected with diphenylhydantoin, carbamazepine, valproic acid or clonazepam for three months immediately after weaning. Following the treatment the fertility of the rats was tested by caging them with proestrus females and recording impregnations. The males were decapitated and their sex organs weighed. Epididymal sperm content and motility rate were recorded. A decrease in the prostate weight was found in the valproic acid and the carbamazepine treated rats. Epididymal weights we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 2 publications
0
21
0
1
Order By: Relevance
“…, 2001). In accordance with this, animal studies have shown altered semen quality after use of different anticonvulsants including phenytoin, carbamazepine and valproate (Cohn et al. , 1982; Taneja et al.…”
Section: Introductionmentioning
confidence: 54%
“…, 2001). In accordance with this, animal studies have shown altered semen quality after use of different anticonvulsants including phenytoin, carbamazepine and valproate (Cohn et al. , 1982; Taneja et al.…”
Section: Introductionmentioning
confidence: 54%
“…A drug-specific effect of valproate also gains some support from the study by Cohn et al 11 in which male rats received different antiepileptic drugs for a period of 3 months. Both carbamazepine treated and valproate treated rats had diminished sperm content, but the valproate treated animals were the only ones with significantly decreased fertility.…”
Section: Discussionmentioning
confidence: 85%
“…Sexual dysfunction, including reduced potency and hyposexuality is seen in as much as 38-71% of men with epilepsy [1][2][3][4] . This may, at least in part, be due to longterm use of AEDs which have been shown to induce disturbances in sex hormone levels 2,[5][6][7][8][9] and also to reduce sperm quality 5,[10][11][12][13] . These effects have so far not been related to specific drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory previously described GABAergic regulation of gonadal activity (Ritta et al, 1987). O n the other hand, GABA A-type binding sites were described on the plasma membrane of spermatozoa (Erdo & Wekerle, 1990), and some authors have reported a direct effect of GABA on sperm viability and motility (Person et al, 1990;Cohn et al, 1982). GABA in reproductive tissues could be derived from different sources: uptake from the bloodstream or peripheral innervation (Erdo & Amenta, 1986;Leader et al, 1992), synthesis from putrescine via the diamine-oxidase or monoamine-oxidase pathway (Seiler, 1980;, and synthesis de novo from glutamic acid via GAD activity (Persson et al, 1990;Tillakaratne et al, 1992).…”
Section: Discussionmentioning
confidence: 99%